МНОГОМЕРНАЯ ГРАНИЧНАЯ ТЕОРЕМА МОРЕРА В КЛАССИЧЕСКОЙ ОБЛАСТИ ПЕРВОГО ТИПА - Отемуратов, Б.П.; Джумабаев, Д.Х.; Кутлымуратов, Б.Ж. (SCIENCE and SOCIETY, 2022)
In this article are obtained boundary variants of Morera's theorem for classical domains of the first type.
Keywords: classical domain of the first type; Shilov bound; normalized Lebesgue measure; automorphisms; analytic disk; Poisson core